Finite Element Analysis of Occupant Risk in Vehicular Impacts into Cluster Mailboxes - Emre Palta; Lukasz Pachocki; Dawid Bruski; Qian Wang; Christopher Jaus; Howie Fang (Computation)
The deployment of cluster mailboxes (CMs) in the U.S. has raised safety concerns for passengers in potential vehicular crashes involving CMs. This study investigated the crashworthiness of two types of CMs through nonlinear finite element simulations. Two configurations of CM arrangements were considered: a single- and a dual-unit setup. These CM designs were tested on flat-road conditions with and without a curb. A 2010 Toyota Yaris and a 2006 Ford F250, both in compliance with the Manual for Assessing Safety Hardware (MASH), were employed in the analysis. The simulations incorporated airbag models, seatbelt restraint systems, and a Hybrid III 50th percentile adult male dummy. The investigations focused on evaluating the safety of vehicle occupants in 32 impact scenarios and under MASH Test Level 1 conditions (with an impact speed of 50 km/h). The simulation results provided insights into occupant risk and determined the primary failure mode of the CMs. No components of the mailboxes were found intruding into the vehicle’s occupant compartment. For all considered cases, the safety factors remained within allowable limits, indicating only a marginal risk of potential injury to occupants posed by the considered CMs.